Bitcoin as an Electronic Payment Tool - Gajdek, Seweryn; Kozak, Sylwester (Management and Administration Journal, 2019)
The article presents the results of research aimed at assessing the Bitcoin (BTC) capability to act as a widely accepted means of payment. The analysis includes technological and economic conditions of the BTC operation system. The research used data on market capitalization, the number of participants and the level of volatility of the BTC exchange rate in 2010-2018 from the portal coinmarketcap.com. The results of the research showed that BTC possesses certain characteristics typical of money, and has the potential to increase its share in the payment system in the future. BTC’s ability to act as an electronic equivalent of cash depends on such factors as the stability of its exchange rate and the level of acceptance among users and payment acceptors. The statistical analysis of the correlation showed that along with the increase in the capitalization value of the BTC market the volatility of the exchange rate of this currency is lowered and the level of acceptance among e-commerce participants is increased. Such dependence will allow for further technological development of BTC and other cryptocurrencies and a wider use in trade.